2002
DOI: 10.1038/sj.eye.6700036
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life in patients with early, moderate and advanced glaucoma

Abstract: Quality of life in patients with early, moderate and advanced glaucoma AbstractPurpose To evaluate the quality of life in glaucomatous patients using two different questionnaires: the medical outcomes study 36-item short-form health survey (MOS SF-36) and Viswanathan et al's questionnaire and to compare these two questionnaires. Methods Seventy-seven patients with glaucoma were consecutively selected. Two force-choice questionnaires were administered to each patient. Viswanathan et al's questionnaire was relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
60
2
5

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(72 citation statements)
references
References 13 publications
4
60
2
5
Order By: Relevance
“…Reduction in QoL of glaucoma patients is well documented in western population [2,7,9,10]. There is hardly any data on these issues from the South Asian region where a large population of the world lives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reduction in QoL of glaucoma patients is well documented in western population [2,7,9,10]. There is hardly any data on these issues from the South Asian region where a large population of the world lives.…”
Section: Discussionmentioning
confidence: 99%
“…This is a potentially dangerous situation while driving because brain cannot recreate sudden or unexpected changes in the scenery ahead. Previous studies have uniformly demonstrated decreased vision specific quality of life and more visual disability in glaucoma patients [2,9,10,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The notion that greater levels of VF loss are associated with greater self-reported difficulty finding the next line of text while reading (performing a returnsweep) has been investigated elsewhere with specific questions [28,29]. In another study, Iester and Zingirian asked patients with glaucoma is if they ''have trouble following a line of print or finding the next line when reading''; interestingly, 60 % of the patients who answered ''yes'' were shown to have a paracentral scotoma [30]. Furthermore, research shows that if the central vision is compromised, there is an advantage in eccentrically fixating during reading such that text falls in the inferior, rather than the superior, VF [31].…”
Section: Discussionmentioning
confidence: 99%
“…Banyak faktor yang berhubungan dengan kualitas hidup penderita glaukoma diantaranya ketidakmampuan penglihatan, masalah minum obat glaukoma, efek samping obat, ketidakcocokan pengobatan, atau kesehatan mental penderitanya. Dalam jangka panjang pengobatan glaukoma sangat diperlukan untuk menambah angka harapan hidup penderitanya (Iester dan Zingrian, 2002).…”
Section: Identifi Kasi Karakteristik Responden Penderita Glaukomaunclassified